Antitumor and apoptotic effects of bergaptol are mediated via mitochondrial death pathway and cell cycle arrest in human breast carcinoma cells (Bangladesh Journal of Pharmacology, 2016)
The aim of the present research work was to investigate the anti-cancer and apoptotic effects of bergaptol in human breast cancer cells (MCF-7). The effects on cell cycle arrest and caspase activation were evaluated. MTT assay was used to evaluate the effect of the compound on cell viability. Cellular morphology was demonstrated by fluorescence microscopy. Flow cytometry was used to analyze effect of bergaptol on cell cycle and apoptosis. The results revealed that bergaptol induced dose-dependent cytotoxic effect on MCF-7 cell viability showing IC50 value of 52.2 µM. Bergaptol induced both early and late apoptosis in concentration-dependent manner. After treatment with bergaptol, an increase in the proportion of cells in the S-phase (37.2, 45.3 and 65.1% as compared to 28.6% in untreated cells) and a reduction in the fraction of cells in the G1 phase (44.1, 41.6 and 35.2% as compared to 51.2% in the untreated cells) was observed.